2017
DOI: 10.1038/s41566-017-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional violation of the shot-noise limit in photonic quantum metrology

Abstract: Quantum metrology exploits quantum correlations to perform measurements with precision higher than can be achieved with classical approaches. Photonic approaches promise transformative advances in the family of interferometric phase measurement techniques, a vital toolset used to precisely determine quantities including distance, velocity, acceleration and various materials properties [1][2][3].Without quantum enhancement, the precision limit in determining an unknown optical phase ϕ-i.e. the minimum uncertain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
239
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(247 citation statements)
references
References 28 publications
8
239
0
Order By: Relevance
“…These developments have provided an an enormous leap forward for SPDC technology, helping it to get close to satisfying many of the criteria (a)-(c) for ideal photon generation. System (heralding) efficiencies jumped 53,133 to above 0.8. The entangled state quality is harder to survey, because of the variety of figures of merits that are used.…”
Section: B Generating a Photonmentioning
confidence: 99%
“…These developments have provided an an enormous leap forward for SPDC technology, helping it to get close to satisfying many of the criteria (a)-(c) for ideal photon generation. System (heralding) efficiencies jumped 53,133 to above 0.8. The entangled state quality is harder to survey, because of the variety of figures of merits that are used.…”
Section: B Generating a Photonmentioning
confidence: 99%
“…Practical designs for ultra-bright sources of quantum light with reduced noise [29] and entanglement together with development of novel principles for engineering practically useful quantum states and measurements [30] have revolutionised photonic quantum sensing. For instance, recent demonstrations have shown the possibilities for multi-photon interferometry beyond the classical limit [31], and it has been shown that weak field homodyning could yield enhanced resolution in phase detection. Early experimental implementations of quantum ellipsometry indicated the high potential of quantum polarisation measurement while the first demonstration of quantum microscopy with NOON states demonstrated the potential of using fragile quantum states in imaging [32].…”
Section: Current Statusmentioning
confidence: 99%
“…The applications of correlations now stretch far beyond their intended use for ghost imaging, also in the frequency domain [102][103][104][105][106][107][108][109][110]. Quantum engineering of phase-sensitive states [16][17][18][19][111][112][113][114][115][116][117][118][119][120] has also been suggested as a way to realise quantum-enhanced two-photon lithography [121][122][123] and microscopy [124]. Intensity squeezing is also being investigated to improve the signal to noise ratio in imaging, by lowering the noise in photon detection below the shot noise limit [125][126][127][128][129][130][131][132][133][134].…”
Section: Applications To Imagingmentioning
confidence: 99%